Mitonuclear Epistasis for Development Time and Its Modification by Diet in Drosophila. Issue 1 (1st May 2016) - Mossman, Jim A; Biancani, Leann M; Zhu, Chen-Tseh; Rand, David M
Abstract: Mitochondrial (mtDNA) and nuclear genes have to operate in a coordinated manner to maintain organismal function, and the regulation of this homeostasis presents a substantial source of potential epistatic ( G × G ) interactions. How these interactions shape the fitness landscape is poorly understood. Here we developed a novel mitonuclear epistasis model, using selected strains of the Drosophila Genetic Reference Panel (DGRP) and mitochondrial genomes from within Drosophila melanogaster and D. simulans to test the hypothesis that mtDNA × nDNA interactions influence fitness. In total we built 72 genotypes (12 nuclear backgrounds × 6 mtDNA haplotypes, with 3 from each species) to dissect the relationship between genotype and phenotype. Each genotype was assayed on four food environments. We found considerable variation in several phenotypes, including development time and egg-to-adult viability, and this variation was partitioned into genetic ( G ), environmental ( E ), and higher-order ( G × G, G × E, and G × G × E ) components. Food type had a significant impact on development time and also modified mitonuclear epistases, evidencing a broad spectrum of G × G × E across these genotypes. Nuclear background effects were substantial, followed by mtDNA effects and their G × G interaction. The species of mtDNA haplotype had negligible effects on phenotypic variation and there was no evidence that mtDNA variation has different effects on male and female fitness traits. Our results demonstrate that mitonuclear epistases are context dependent, suggesting the selective pressure acting on mitonuclear genotypes may vary with food environment in a genotype-specific manner.